The slowly turning wheels on mother tongue-based bilingual education (MTbBE) finally stopped - August-Mowers, C. M. (South African Journal of Higher Education, 2025)
It was déjà vu in South Africa for scholars, particularly in language education, when President Cyril Ramaphosa announced the implementation of the Basic Education Laws Amendment (BELA) Act and the Mother Tongue-based Bilingual Education (MTbBE) this year. The announcement came at a favourable time, as the world prepared for UNESCO’s celebration of International Mother Tongue Language Day on 21 February 2025. Advocacy for multilingualism has been a topic of interest for many years, and the slow wheels have turned in response to the call of MTbBE. However, the readiness of the South African Education system to accommodate MTbBE remains an unsolved puzzle. This article underscores the role of MTbBE in multilingual contexts, highlighting linguistic diversity as a fundamental human right. The study adopted a qualitative research method through a literature review by evaluating existing language ideologies and language practices that challenged the unfinished project of decolonial education in South Africa. This study aims to provide a comprehensive overview of language ideologies and policy lag that condition multilingualism and its implementation in MTbBE. At the same time, it proposes practical strategies such as translanguaging to respond to multilingual needs. Higher institutions of learning have responded well to the MTbBE call. As such, the University of Cape Town (UCT) launched their newly approved multilingual policy on 27 February, and the University of the Western Cape (UWC) is actively reviewing its language policy. The Western Cape Education Department (WCED) announced the Mother Tongue-based Bilingual Education (MTbBE) rollout on 7 April 2025. One can expect that all other institutions of learning would answer the call as it aims to address the salient and underlying language issues of the inherent past. I contend that language should be recognised as a fundamental human right. I, therefore, posit that it is a collective responsibility to uphold this right as a social justice imperative. Belonging to cultural and linguistic communities is affirmed in the Bill of Rights, including equality and human dignity. The UBUNTU philosophy is thus central to this paper as its characteristics align with my vision to encourage education practices that are culturally and linguistically responsive.